Effects of Music Training on Attention, Processing Speed and Cognitive Music Abilities—Findings from a Longitudinal Study. Issue 4 (2nd July 2014) - Roden, Ingo; Könen, Tanja; Bongard, Stephan; Frankenberg, Emily; Friedrich, Esther Kamala; Kreutz, Gunter
Summary The present study addresses visual attention and processing speed in primary school children (N = 345; 7–8 years of age) who received either music (MC) or natural science training (NC) over a period of 18 months. Dependent variables were collected three times (T1–T3) and included measures for processing speed, visual attention and cognitive music abilities. They were submitted to latent or manifest change models including socioeconomic status and basic cognitive functions as covariates. Groups performed similarly in all dependent tasks at baseline (T1). MC showed significant increases in processing speed as well as in music abilities from T2 to T3 and increases in rhythmic abilities from T1 to T2. Although MC also showed increases in both processing speed and visual attention over time, they were at a small advantage with respect to the former and at a clear disadvantage with respect to the latter measure as compared to NC. Copyright © 2014 John Wiley & Sons, Ltd.